THE RELATIONSHIP BETWEEN NURSES' CARING BEHAVIOR AND FAMILY ANXIETY LEVELS OF CRITICAL PATIENTS IN THE INTENSIVE CARE UNIT (ICU) ROOM DR. ADJIDARMO LEBAK HOSPITAL IN 2023 - Riyanti, Tetik; Kusnanto, Kusnanto (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Intensive Care Unit (ICU) is one part of the hospital that provides nursing services to patients in critical condition with trained staff and special equipment so as to trigger an anxiety response in the family of critical patients. One of the efforts that can be made to reduce anxiety levels in families of critical patients is by providing holistic nursing care through a behavioral caring approach. Purpose: To determine the relationship between nurses' caring behavior and the anxiety level of critical patients' families in the Intensive Care Unit (ICU) room of Dr. Adjidarmo Lebak Hospital in 2023. Methods: Descriptive with a research design using cross-sectional approach. Results: Obtained from 32 respondents, most respondents rated nurses' caring behavior with good categories (90,6%) and most respondents (65,6%) did not experience anxiety, a small number experienced mild anxiety (25,0%) and moderate anxiety (9,4%), and there is a relationship between the caring behavior of nurses and the level of anxiety of critical patients' families in the Intensive Care Unit Room of Dr. Adjidarmo Lebak Hospital in 2023 (p-value = 0,039). Where the higher the nurse's caring behavior, the lower the respondent's anxiety level. Conclusion: It is expected to provide nursing care that not only focuses on therapy but thinks about psychological aspects, namely by providing counseling interventions where the patient's family can exchange ideas with health workers about the problems experienced by patients so as to improve the quality of nursing care holistically.